Composite light-harvesting materials and devices
By introducing luminescent materials into organic semiconductors, the band gap resonance between the triplet exciton formed by multi-exciton generation and the inorganic luminescent material is achieved, and the energy transfer of triplet excitons is solved, which solves the problem of low energy transfer efficiency between organic semiconductors and inorganic semiconductors and improves the efficiency of solar cells.
Patent Information
- Application Number
- CN202011044224.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2014-07-15
- Filing Date
- 2015-07-15
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2035-07-15
AI Technical Summary
The prior art is difficult to effectively realize the energy transfer between organic semiconductors and inorganic semiconductors, especially the energy transfer of triplet excitons, limiting the efficiency of solar cells.
By introducing a luminescent material into an organic semiconductor, the band gap resonates with the inorganic luminescent material formed by multi-exciton generation, thereby realizing the transfer of the Dexter energy of the triplet exciton into the inorganic luminescent material.
The energy transfer efficiency between organic semiconductors and inorganic semiconductors is improved, the photocurrent and photovoltaic voltage of solar cells are enhanced, exceeding the Shockley-Quiser limit.
Smart Images

Figure CN112420930B_ABST
Abstract
Description
[0001] This application is a divisional application of an application filed on July 15, 2015, with application number 201580037978.8 and invention name “Composite light-harvesting materials and devices”.
[0002] The present invention generally relates to compositions of organic semiconductors capable of multiple exciton generation. Specific compositions can be used in photovoltaic devices and light emitting devices to give improved efficiency.
[0003] The efficiency of conventional solar cells is limited to about 34%, mainly due to thermalization of above-bandgap photons and transmission of below-bandgap photons. The efficiency limit is known as the Shockley-Queisser limit.
[0004] Many strategies have been used to make solar cells that exceed the Shockley-Queisser limit. Such strategies can include the use of organic and inorganic tandem cells. However, in these designs, matching the currents of the sub-cells has been challenging. Efficient transfer of energy between organic and inorganic semiconductors is a widely sought property for applications in photovoltaics (PV), light-emitting diodes, and sensors. To date, efforts to couple organic and inorganic semiconductors have focused on singlet excitons via Förster resonance and energy transfer ( resonance and energy transfer) (FRET).
[0005] US 2010 / 0193011 A (MAPEL et al.) 05 / 08 / 2010 discloses a solar concentrator that improves the efficiency of PV cells. The solar concentrator includes an emitting chromophore effective for accepting at least some energy from another chromophore by Forster energy transfer. The emitting chromophore emits some of the received energy at a wavelength that is red-shifted from the wavelength absorbed by the other chromophore.
[0006] Another strategy for making solar cells that exceed the Shockley-Queisser limit is disclosed in EHRLER, Bruno, et al. Singlet Exciton Fission-Sensitized Infrared Quantum Dot Solar Cells. NanoLett.. 2012, Vol. 12, pp. 1053-1057. Ehrler et al. demonstrated an organic / inorganic hybrid photovoltaic device configuration that uses singlet exciton fission to allow two electrons to be collected per absorbed high-energy photon while capturing low-energy photons. Singlet exciton fission is an established process in organic semiconductors by which a singlet exciton generated by light couples to a neighboring molecule in the ground state, generating two triplet excitons. The transfer of triplet excitons is desirable because triplet excitons have properties such as long lifetimes of up to several ms and diffusion lengths of up to several μm. However, the transfer of triplet excitons via Forster resonance energy transfer is spin-forbidden, as discussed in SCHOLES, GD, et al. Long range resonance energy transfer in molecular systems. Annual review of physical chemistry. 2003, Vol. 54, pp. 57-87. In the device of Ehrler et al., infrared photons are absorbed using lead sulfide (PbS) nanocrystals. Visible photons are absorbed in pentacene to produce singlet excitons, which undergo rapid exciton fission to produce paired triplet states. Each of the two triplets can generate an electric charge after dissociation at an organic / inorganic heterojunction, which means that the direct effect of singlet fission in solar cells is to double the photocurrent while halving the maximum possible photovoltage.
[0007] Therefore, there is a need to further improve the coupling of organic and inorganic semiconductors and to enable efficient energy transfer between them. Additionally, there is a need to identify conditions under which triplet excitons can undergo efficient energy transfer to inorganic semiconductors.
[0008] Therefore, it is an object of the present invention to provide a composite light-harvesting material that can couple organic and inorganic semiconductors together using energy transfer of triplet excitons. The composite light-harvesting material has applications in photovoltaics (PV), light-emitting diodes, lasers, and sensors.
[0009] According to a first aspect of the present invention, a composite material is provided that includes a main organic semiconductor material, wherein the main organic semiconductor material is capable of generating multi-excitons dispersed by a light-emitting material; wherein the band gap of the light-emitting material matches the energy of triplet excitons formed due to the generation of multi-excitons, so that the triplet excitons are resonant with the band gap of the inorganic light-emitting material.
[0010] Hereinafter, the present inventors demonstrate that triplet excitons can be transferred from an organic semiconductor to a light-emitting material via Dexter energy transfer. Triplet excitons formed due to multi-exciton generation in an organic semiconductor are transferred from the organic semiconductor to a light-emitting material via non-radiative energy transfer.
[0011] According to a second aspect of the present invention, a photovoltaic device is provided, wherein the composite material is combined with a photovoltaic cell so that light emission from the composite material falls on the photovoltaic cell. Therefore, according to a second aspect of the present invention, a photovoltaic device is provided comprising an organic semiconductor photoactive layer capable of multi-exciton generation with a luminescent material dispersed therein; wherein the band gap of the luminescent material is selected to match the energy of triplet excitons formed due to multi-exciton generation, so that the triplet excitons are resonant with the lowest optical absorption band (herein referred to as the band gap) of the luminescent material; the photovoltaic cell is arranged in the emission light path of the inorganic luminescent material and has a first photoactive layer, wherein the band gap of the luminescent material matches the band gap of the first photoactive layer or is higher than the band gap of the first photoactive layer.
[0012] Preferably, the organic semiconductor photoactive layer is capable of singlet exciton fission. Examples of such organic semiconductor materials are polyacenes or oligoacenes, optionally pentacene, tetracene or a derivative thereof selected from the group consisting of bis(triisopropyl-silylethynyl)pentacene (TIPS-P), diphenylpentacene (DPP), dibiphenyl-4-yl-pentacene (DBP), di(2'-thienyl)pentacene (DTP), and dibenzothienylpentacene (DBTP), bis(triisopropyl-silylethynyl)pentacene (TIPS-P), bis((triethyl)ethynyl)pentacene (TES-P) or rubrene, bis(triisopropyl-silylethynyl)tetracene (TIPS-T), di(2'-thienyl)tetracene (DTT).
[0013] Preferably, the organic semiconductor photoactive layer has a band gap in the range of 2.0 eV to 2.6 eV, preferably in the range of 2.2 eV to 2.5 eV, more preferably 2.4 eV.
[0014] The band gap of the light emitting material is preferably within 0.4 eV, preferably within 0.3 eV, more preferably within 0.2 eV of the band gap of the energy of the triplet excitons.
[0015] Preferably, the band gap of the light emitting material is in the range of 0.6 eV to 1.6 eV, preferably in the range of 0.75 eV to 1.3 eV, more preferably in the range of 0.95 eV to 1.1 eV.
[0016] Advantageously, the luminescent material comprises an inorganic material, preferably a nanocrystalline semiconductor. In this case, the nanocrystal can comprise a lead chalcogenide nanocrystal such as lead selenide or lead sulfide. Other selections of nanocrystal semiconductors can comprise any one or more of the nanocrystal, which nanocrystal comprises: CdSe, CdS, ZnTe, ZnSe, PbS, PbSe, PbTe, HgS, HgSe, HgTe, HgCdTe, CdTe, CZTS, ZnS, CuInS2, CuInGaSe, CuInGaS, Si, InAs, InP, InSb, SnS2, Ge, CuS, and Fe2S3.
[0017] The photovoltaic device can be arranged so that the light harvesting device includes an organic semiconductor photoactive layer capable of multi-exciton generation with a light-emitting material dispersed therein; wherein the band gap of the light-emitting material is selected so that triplet excitons formed due to multi-exciton generation in the organic semiconductor can be transferred from the organic semiconductor to the light-emitting material, wherein at least one step is mediated by non-radioactive Dexter energy transfer. In this way, mediation can be provided by intermediate steps of different energy transfer mechanisms, provided that at least one step is mediated by non-radioactive Dexter energy transfer.
[0018] As part of a photovoltaic device, a light harvesting device may include an organic semiconductor photoactive layer capable of multi-exciton generation with light-emitting nanocrystals dispersed therein; wherein the band gap of the nanocrystals is selected so that triplet excitons formed due to multi-exciton generation in the organic semiconductor can be transferred from the organic semiconductor to the nanocrystals, wherein the final energy transfer step into the nanocrystals is mediated by non-radioactive Dexter energy transfer. Likewise, when the final energy transfer step into the nanocrystals is by non-radioactive Dexter energy transfer, the previous steps or hops or energy transfers from the organic semiconductor material may occur by alternative means including Forster resonance and energy transfer as well as via other materials.
[0019] Preferably, the photon multiplier system comprising a film and containing the composite material described above is provided with at least one light-directing element to preferentially direct light emitted from the luminescent material towards one or a selection of a surface or an edge.
[0020] Preferably, the organic semiconductor is acene, acene dimer, perylene, perylene dimer, perylene diimide, terylene, terrylene, thiophene, or a semiconducting polymer.
[0021] Preferably, suitable choices for nanocrystalline semiconductors include any one or more of nanocrystals including organometallic halide perovskites or cesium lead halide perovskites.
[0022] In the device, the photovoltaic cell is preferably provided with a first photoactive layer comprising amorphous silicon. Optionally, the photovoltaic cell is provided with a first photoactive layer comprising crystalline silicon, copper indium gallium selenide (CIGS), germanium, CdTe, GaAs, InGaAs, InGaP, InP or a perovskite semiconductor such as an organometallic halide perovskite semiconductor and more specifically methylamine lead chloroiodide (CH3NH3PbI2Cl).
[0023] Preferably, the nanocrystalline semiconductors are passivated by ligands which dissolve them in a solvent compatible with the organic semiconductor, preferably a small molecule, more preferably an amine or thiol.
[0024] Preferably, the average distance between luminescent components is chosen to be similar to the diffusion length of triplet excitons in the organic semiconductor; wherein a low concentration of luminescent components is necessary to minimize self-absorption by the luminescent components.
[0025] More preferably, the average distance between the organic semiconductor and the light emitting material is between 10 nm and 2000 nm, more preferably between 20 nm and 200 nm.
[0026] More preferably, the average distance between the luminescent components is between 10 nm and 2000 nm, more preferably between 20 nm and 200 nm.
[0027] To further increase the efficiency of the device and capture any photons emitted in the direction towards the photovoltaic cell, the organic semiconductor photoactive layer is preferably provided with a layer that directs light towards the photovoltaic cell. Preferably, this layer is a selective wavelength reflective layer or one in which the refractive index of a layer of the device is adjusted to direct emission from the composite light harvesting device towards the photovoltaic cell.
[0028] According to a third aspect of the present invention, a light-emitting device is provided, which includes an organic semiconductor layer and an inorganic light-emitting material dispersed therein; wherein the band gap of the inorganic light-emitting material is selected to match the energy of triplet excitons formed by injecting charges into the organic semiconductor layer, so that the triplet excitons are resonant with the band gap of the inorganic light-emitting material.
[0029] In each aspect of the invention and preferred embodiments described herein, band gap means that the triplet excitons are resonant with the lowest optical absorption band. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Embodiments of the present invention will now be described, by way of example only, and with reference to the accompanying drawings, in which:
[0031] Figure 1 It is a schematic diagram of singlet fission down conversion;
[0032] Figure 2 is a schematic diagram of the device structure;
[0033] Figure 3 is a graph of the external quantum efficiency of a device according to a first embodiment of the present invention compared to various controls;
[0034] Figure 4 (a) is a schematic diagram of singlet exciton fission in pentacene;
[0035] Figure 4 (b) is a schematic diagram illustrating how an inorganic solar cell can be sensitized by singlet fission using triplet transfer from a thin organic singlet fission layer;
[0036] Figure 4 (c) is a schematic diagram of the possible processes that triplet excitons can undergo at the organic / inorganic interface;
[0037] Figure 4 (d) is a graph comparing the dynamics of pristine pentacene and a bilayer with lead selenide nanocrystals in the pentacene state.
[0038] Figure 5 (a) is the transient absorption spectrum (TA) of pentacene with a lead selenide double layer. Figure 5 The data in (a) are decomposed into three excited states, where the spectra are given by Figure 5 The solid line in (b) shows the corresponding population dynamics in Figure 5 (c) is shown;
[0039] Figure 5 (d) Illustration of the blue shift of the ground state bleaching (GSB) peak of lead selenide nanocrystals;
[0040] Figure 6 (a) is a graph of the normalized dynamics of the pentacene spectral component extracted via GA from transient absorption data of pentacene and lead selenide bilayers with varying nanocrystal band gaps;
[0041] Figure 6 (b) Yes Figure 6 (a) PbSe spectral composition corresponding to the graph;
[0042] Figure 6 (c) is a schematic diagram of the range of nanocrystal band gaps over which triplet state transfer is observed for pentacene to lead selenide bilayers;
[0043] Figure 7 (a) is a photoluminescence image of a double-layer film of lead selenide, pentacene, and lead selenide;
[0044] Figure 7 (b) is a graph showing the photoluminescence enhancement from lead selenide versus pentacene absorption; and
[0045] Figure 8 Schematic diagram of a light-emitting diode based on triplet state transfer to inorganic nanocrystals. DETAILED DESCRIPTION
[0046] according to Figure 1 In the first embodiment of the present invention, the composite material 10 includes a thin film of an organic material 12 capable of singlet fission mixed with an inorganic nanocrystal 14. The optical absorption of a high energy photon 16 in the organic material 12 generates a singlet exciton 18, which rapidly undergoes singlet fission to form two triplet excitons 20. Due to the spin selection rule, the triplet exciton 20 cannot be emitted. However, the triplet exciton 20 will diffuse into the inorganic nanocrystal 14 and undergo an efficient Dexter energy transfer into the inorganic nanocrystal 14. Then, the electron-hole pairs in the inorganic nanocrystal 14 can be radioactively recombined, thereby emitting a photon 22. Therefore, each high energy photon 16 absorbed by the organic material 12 can cause two low energy photons 22 to be emitted through the nanocrystal 14. The low energy photon 24 passes through the organic material 12.
[0047] Photons 22 emitted by nanocrystals 14 may be detected, for example, in Figure 2 26 provided in the adjacent solar cell 26. A light capture layer 28, such as a selective reflector 28, can be used so that it reflects photons 22 emitted by the nanocrystals 14 to enhance the coupling of light into adjacent solar cells. This is a way to convert energy from one high-energy photon 16 into two low-energy photons 22 that match the band gap of the solar cell 26, thus doubling the current generated from the high-energy photon 16.
[0048] refer to Figure 3, we illustrate the first embodiment of the invention using TIPS-tetracene molecules. PbSe quantum dots with a 1.1 eV bandgap were embedded in a TIPS-tetracene body (10% by weight), and the EQE of a silicon solar cell was observed. Trace 1 is the external quantum efficiency of a silicon solar cell, and Trace 2 is a silicon solar cell in which a film of the composite material is in the light path. Using a filter between the composite material layer and the solar cell, low energy photons including those emitted by the nanocrystals can be filtered out (Trace 3), and in Trace 4, the ratio of Trace 2 and Trace 3 with and without the filter reveals that the additional current generated by the nanocrystal emission in the infrared originates from the absorption of the organic singlet fission sensitizer in the visible light.
[0049] Figure 3 The spectrum in trace 2 shows a clear dip at the tetracene absorption and when a filter that removes light emitted by the nanocrystals is placed between the tetracene film and the silicon solar cell as shown in trace 3, the overall efficiency drops. Crucially, the spectrum drops even more at the tetracene absorption, which identifies additional current from triplet transfer in trace 4.
[0050] Thus, in a first embodiment of the invention, the inventors have demonstrated efficient resonance-energy transfer of molecular spin triplet excitons from organic semiconductors to inorganic semiconductors. In the following description, we also demonstrate the physical process behind the transfer using ultrafast optical absorption spectroscopy to track the dynamics of triplet states generated via singlet exciton fission in pentacene at the interface with lead selenide (PbSe) nanocrystals. We show that triplet states are rapidly (<1ps) and efficiently transferred to PbSe, with 1.8 triplets transferred for each photon absorbed in pentacene. Triplet transfer is most efficient when the band gap of the nanocrystal is close to resonance with the triplet energy (±0.2eV). After triplet transfer, the excitons can undergo charge separation, which allows photovoltaic operation; or radioactive recombination in the nanocrystal, which enables luminescent capture of triplet exciton energy in the light-emitting structure.
[0051] Example
[0052] Singlet exciton fission (SF) is a process in inorganic semiconductors by which a single photogenerated spin-singlet exciton is converted into two spin-triplet excitons on a nearby chromophore. Because the process is spin-allowed, it can occur with 200% efficiency in a sub 100fs timescale when the energetics of the system are favorable, i.e., the energy of the spin-singlet exciton is greater than or equal to twice the energy of the spin-triplet exciton. If SF materials can be suitably combined with low-bandgap inorganic semiconductors, SF is a promising approach to overcome the Shockley-Queisser limit in single-junction photovoltaics.
[0053] Therefore, reference Figure 4 (a), Singlet exciton fission in pentacene is schematically demonstrated, where a photogenerated singlet exciton S1 undergoes singlet fission SF into two triplet excitons 20 with a time T1 within 80 fs.
[0054] exist Figure 4 In this configuration illustrated in (b), for each low-energy photon 24 absorbed, the low-bandgap semiconductor 26 generates one electron-hole pair, while for each high-energy photon 16 absorbed, the SF material 12 generates two triplet excitons 20. By distributing the energy of the high-energy photon 16 into two excitations, SF can allow solar cells to overcome otherwise major thermalization losses. Ideally, the energy of the triplet exciton 20 can be directly transferred to the inorganic semiconductor 26, for which charge generation and collection are already optimized. This approach allows the SF material to act as an energy-funnelling layer on top of a conventional photovoltaic cell, rather than an active part of the circuit.
[0055] Pentacene (Pc) is a model system for singlet exciton fission. Previous transient optical absorption (TA) measurements on Pc determined a fission rate of 80 fs, outperforming alternative decay mechanisms. The fission-generated triplet states can be efficiently dissociated at the heterojunction using the fullerene C60 as an acceptor, allowing an external quantum efficiency (EQE) of 126%, the highest for any photovoltaic technology to date. There are two possible pathways for charge generation at such an organic / inorganic interface, such as Figure 4 The first is the electron transfer (ET) from Pc to PbSe. The second is the triplet exciton energy transfer (triplet transfer TT) into PbSe, followed by hole transfer back (hole transfer HT) into Pc to obtain charge separation.
[0056] result
[0057] To study the dynamics of Pc triplet excitons at the interface with PbSe, the inventors performed TA measurements on thin PbSe / Pc bilayers consisting of 1-2 monolayers of spin-coated PbSe, onto which 5 nm of Pc (3 molecular layers) were evaporated. The thinness of the pentacene layer ensured that all triplet excitons were generated close to the interface with PbSe. This allowed the inventors to probe the interface dynamics, which are usually masked by bulk diffusion processes. The samples were studied with femtosecond (fs) TA spectroscopy using narrowband pump pulses focused at 550 nm and broadband probe pulses. To amplify the signal from extremely thin layers, we used an optical cavity that allowed multiple passes of a collinear pump and probe beam through the sample. A series of PbSe nanocrystals with bandgap energies between 0.67 eV and 1.61 eV were compared with Pc.
[0058] Figure 4 (d) Comparison of TA dynamics at 670nm for original Pc and Pc / PbSe double layers of nanocrystals with varying band gaps. 670nm is the location of the peak of the Pc ground state bleaching (GSB). The molecular triplet exciton (T1) in the lowest state of Pc has been reported to be at nearly 0.86eV. Two double layers of nanocrystals with a band gap far below this energy (0.67eV) and a band gap above this energy (1.61eV) show almost the same dynamics as the original Pc film. In contrast, a double layer of nanocrystals with a band gap of 0.78eV close to resonance with T1 shows a significant reduction in the signal within the first 2ps, followed by recovery at a later time. As we have developed below, this kinetic behavior is due to energy transfer, de-excitation of the chromophore, followed by back charge transfer, re-excitation of the chromophore.
[0059] However, before we can quantify the excited state population, the presence of excited state signals from PbSe needs to be considered. Figure 5 (a) shows the TA spectrum of a Pc / PbSe (0.78 eV) bilayer. To extract the individual spectra and population dynamics of the various excited state species, we used a genetic algorithm. Figure 5 The data in (a) can be decomposed into three excited states, where the spectrum is given by Figure 5 The solid line in (b) shows the corresponding population dynamics in Figure 5(c) is shown. One component 50 matches the expected signal for Pc, as demonstrated by the consistency with the spectrum of the original Pc film (dashed spectrum 52). We note that after the ultrafast fission process (80fs), there is no spectral evolution in the signal from Pc. Therefore, in the experiment provided here, at a time resolution>300fs, only a single spectrum is expected for Pc. Nanocrystals show two distinguished spectra in this region (solid lines 54, 56), which are related to relaxation from a higher energy excited state to a lower energy excited state, as demonstrated by the early signal and late signal (dashed spectrum 58, 60) from the original PbSe film.
[0060] We now turn to Figure 5 The dynamics extracted by the genetic algorithm shown in (c) represent the weight of the spectral components of the excited state species in the entire data set, rather than the dynamics at a specific spectral point. We observe that the Pc component of the Pc / PbSe (0.78eV) film (50) decreases faster than the original Pc film (dashed line 52) in the initial 0.3-3ps, but then rebounds and has a larger signal than the original Pc film later (>30ps). We can observe that at the earliest time (300fs), the population of Pc is entirely composed of triplet excitons, which is due to the ultrafast (80fs) fission process. Therefore, the reduction in signal between 0.2-3ps represents the loss of triplet excitons. The increase in the signal later is consistent with the transfer of holes from PbSe to Pc. The rise in the lower energy excited state component of PbSe, curve 62, is related to the decrease in the higher energy PbSe excited state component (curve 54) and the loss of triplets in Pc. This suggests that both processes can populate lower energy PbSe excited states.
[0061] Finally, we observed a blue shift in the GSB peak of PbSe nanocrystals, Figure 5(d). We consider that this shift is caused by charge transfer across the Pc / PbSe interface, which establishes a microscopic electric field, causing a Stark shift in the transient energy of the material near the interface. This leads to a derivative-like feature at the red edge of the absorption feature, known as electroabsorption. The blue shift of the GSB occurs within tens of ps, and therefore, the related charge transfer process occurs within tens of ps. This period coincides with the rebound of the Pc component, confirming that this rise is attributed to the hole rotation from PbSe. For the original PbSe layer or Pc / PbSe double layer in which no triplet transfer was observed, no electroabsorption feature or displacement of the GSB was observed. Therefore, the model that emerges from the data is one of forward transfer from the Pc triplet to PbSe, followed by hole rotation from PbSe to Pc.
[0062] Therefore, if Figure 5 As shown in (a), we show the transient absorption (TA) spectrum of a Pc / PbSe (0.78 eV) film. The spectrum was averaged over the indicated pump-probe delay. For the first pass, the pump fluence was 30 μJ cm -2 , and for the last pass, the pumping volume was 0.4 μJ cm-2. The TA data can be numerically decomposed into 5 components using a genetic algorithm (GA) and Figure 5 (a) to 5(d) are shown.
[0063] Figure 6 (a) shows the normalized kinetics of the Pc component extracted via GA for both pristine Pc films and Pc / PbSe bilayers with varying nanocrystal band gaps. Figure 6 (b) shows the corresponding PbSe composition of both the original nanocrystal film and the Pc / PbSe bilayer. The initial triplet transfer and subsequent hole transfer are only observed at the nanocrystal band gap of 0.78 eV, Figure 6 (a) In the other two cases, for nanocrystals with much higher or lower band gaps than the Pc triplet energy (0.86 eV), the dynamics are almost the same as the pristine pentacene film, indicating very little or no triplet transfer.
[0064] Turning to the PbSe component, Figure 6(b), for the 0.67 eV nanocrystals where no triplet transfer is observed, there is only a small difference between the original PbSe (dashed line 72) and the Pc / PbSe (solid line 74). However, for the 0.78 eV nanocrystals where triplet transfer is observed, there is a large enhancement of the signal for the Pc / PbSe sample (solid line 70) compared to the original PbSe (dashed line 68). The signal peaks 4-5 ps later, corresponding to the period of triplet transfer ( Figure 6 (a)). This shows that the signal enhancement is due to the transfer of triplet states to PbSe. The population is also found to be longer-lived, consistent with the formation of longer-lived charges after hole rotation. In summary, Figure 6 In (c), we found that triplet transfer (TT) from Pc occurs most efficiently in nanocrystals with band gaps of 0.78 eV or 0.93 eV. Nanocrystals whose band gaps are within a narrow range (less than ±0.2 eV) of the triplet energy of Pc (0.86 eV) show the most efficient triplet transfer.
[0065] The narrow energy range in which triplet transfer occurs most efficiently indicates the importance of the overlap of the density of states of the donor and acceptor. The coupling integral for the energy transfer process includes contributions from both the Coulomb interaction and the exchange interaction. The negligible oscillator strength of the S0→T1 transition of Pc means that the Coulomb interaction does not play a significant role in the process. For the exchange interaction, DEXTER, DLA Theory of Sensitized Luminescence in Solids. The Journal of Chemical Physics. 1953. deduced:
[0066]
[0067] where k is the transfer rate, L is the orbital radius of the donor and acceptor sites, R is the spacing between the donor and acceptor and J is the normalized spectral overlap between the donor emission and the acceptor absorption.
[0068] Importantly, J is independent of the oscillator strength of the optical transition. Therefore, triplet transfer will only be effective for nanocrystals whose lowest energy absorption feature overlaps with the S0→T1 transition of Pc at about 0.8 eV, which has a large density of states. The width of the lowest energy absorption feature of the nanocrystals studied here is about 0.15 eV, which corresponds well to the narrow range (less than ± 0.2 eV) in which triplet transfer is observed.
[0069] For the Pc / PbSe system studied here, triplet transfer can be followed by hole rotation. But the excited part may not undergo hole transfer and recombine within PbSe. In addition, at a later time, electron-hole recombination of states previously separated across the interface will occur. Both cases allow radioactive recombination and thus enhance emission from PbSe, regardless of whether triplet transfer is possible. Figure 7 (a) shows the PL spectra of PbSe films and Pc / PbSe films for excitations above (532nm and 650nm) the Pc band gap and below (780nm and 808nm) the Pc band gap. The red shift of the PL peak of the double layer is caused by the red shift of the absorption onset of PbSe of the Pc / PbSe film compared to the original PbSe film. In all cases, Pc / PbSe shows enhanced PL compared to the original PbSe. We believe that the enhanced PL for below-gap excitations (780nm and 808nm) arises from enhanced radioactive recombination in the presence of Pc, which is due to changes in the local environment of PbSe. We normalize the PL signal using the ratio of the PL of Pc / PbSe to the PL of PbSe at 808nm (a factor of 36.5). This allows us to consider enhanced radioactive recombination, which should be independent of the pump wavelength, and to separate the enhanced PL arising from triplet transfer. After normalization, no change in the relative PL was seen at 780 nm, but much stronger PL was seen at 650 nm and 532 nm.
[0070] As in Figure 7 As shown in (b), the stronger PL is related to Pc absorption, which confirms that PL is increased due to triplet energy transfer from Pc. Near the peak of Pc absorption, at 650nm, Pc / PbSe (0.93eV) double layer absorbs 47% more light than PbSe (0.93eV) film (see S10). Crucially, at this wavelength, PL is enhanced by 85%. This means that every photon absorbed by Pc1.8 excitation contributes to PL. As shown above, triplet transfer is the main process in the double layer. Assuming that singlet fission is carried out with a 200% yield of triplet, this means a minimum triplet transfer efficiency of 90%. For Pc / PbSe samples in which the nanocrystal band gap prevents triplet transfer, no PL enhancement caused by the excitation of Pc is observed, which further proves that the enhancement is not due to the early (sub 100fs) transfer of singlet excitation via FRET. We note that by appropriate choice of SF materials and inorganic acceptors, it would be possible to arrange the energy so that hole rotation is prevented, thereby allowing only triplet transfer.
[0071] Finally, we have reported the first demonstration of triplet energy transfer from organic semiconductor to inorganic semiconductor. Our study of the photophysics of thin double-layer samples of pentacene / PbSe nanocrystals proves that triplet energy transfer from pentacene to PbSe is effective only when the nanocrystal band gap is resonant with the molecular triplet energy. This result opens a new avenue for coupling organic semiconductors and inorganic semiconductors and a new possibility for devices. For example, for utilizing non-radioactive triplet excitons produced via charge injection into organic LEDs. Triplet states can be captured via transfer to inorganic nanocrystals where electron-hole pairs can be radioactively recombined, which allows white light emission without the need for phosphorescent molecules. As demonstrated here, this process can also be used to utilize triplet excitons produced via singlet exciton fission, thereby allowing the energy of triplet states to be directly gathered in conventional inorganic solar cells. This provides a very promising method for overcoming Shockley-Queisser limitations.
[0072] method
[0073] Nanocrystal preparation: If not stated otherwise, all chemicals were purchased from Sigma Aldrich and were anhydrous if commercially available. PbSe nanocrystals were synthesized following Standard Method 20. Briefly, Pb(OAc)2H2O (3.44 mmol; 1.3 g), oleic acid (OA; 8.58 mmol; 2.7 ml) and 1-octadecene (ODE; 75 mmol; 24 ml) were degassed at 100°C under vacuum (10-2 mbar or better) for 2 h. To form the Pb-oleate precursor complex, the temperature was raised to 160°C under nitrogen atmosphere and then changed to the desired Se-precursor injection temperature (120°C-180°C). In parallel, Se (Alfa Aeser, 10.8 mmol; 852.8 mg), diphenylphosphine (DPP; 15 μmol; 26.1 μl) and tri-n-octylphosphine (TOP; 24.2 mmol; 10.8 ml) were combined and stirred under nitrogen atmosphere to form a Se-precursor. PbSe nanocrystal growth was initiated by rapid injection of the Se-precursor into the prepared Pb-oleate solution. After reaching the desired nanocrystal size (20 sec-5 min), the reaction was quenched by injecting 20 ml of hexane and by placing the flask in an ice-cooled water bath. Subsequent purification steps were performed in an argon-filled glove box. The nanocrystals were extracted via repeated precipitations with a mixture of 1-butanol and ethanol.
[0074] Sample preparation: The samples were prepared on 0.13 mm thin cover glass slides. The nanocrystal film was deposited by a layer-by-layer method from a 5 mg / mL solution of PbSe in an inert environment using 1,3-benzenedithiolate as a crosslinking molecule. Subsequently, 5 nm of pentacene was deposited on the nanocrystal film at a depth of better than 2 × 10 -6 The sample was then sealed with a second 0.13 mm thin glass slide and epoxy glue before being exposed to air.
[0075] Steady-state optical measurements: Absorption spectra of nanocrystals were taken in solution at 0.05–1 mg / mL using a PerkinElmer Lambda 9UV VisIR spectrometer. PL was measured by illuminating a spot of approximately 2 mm in diameter with a diode laser (MGL-III-532 for 532 nm; SMFR-R0004 for 650 nm; Lasermax-MDL for 780 nm; IQu1C135 for 808 nm). A lens projects the PL with a solid angle of emission of 0.1π onto an InGaAs detector (Andor DU490A-1.7) with a cut-off at 1600 nm.
[0076] Transient Absorption (TA) Spectroscopy: In this technique, a pump pulse generates photoexcitation within the film, which is then studied at some later time using a broadband probe pulse. A portion of the output of a Ti:Sapphire amplifier system (Spectra-Physics Solstice) operating at 1 KHz is used to pump a TOPAS optical parametric amplifier (LightConversion) to produce narrowband (10 nm FWHM) pump pulses focused at 550 nm. Another portion of the amplifier output is used to pump a homemade non-collinear optical parametric amplifier (NOPA). The probe beam is split to produce a reference beam so that laser fluctuations can be normalized. The pump and probe beams are made collinear with a beam splitter and enter an optical cavity consisting of two concave lenses (focal length f) placed 4f apart from each other with the sample in the center. The beam undergoes multiple bounces in the cavity, resulting in multiple passes in the sample, allowing weak signals from the thin layer to be amplified. After leaving the cavity, a long pass filter is used to block the pump beam while allowing the probe beam to pass. The probe beam and reference beam are dispersed in a spectrometer (Andor, Shamrock SR-303i) and detected using a pair of 16-bit 512-pixel linear image sensors (Hamamatsu). The detection is delayed using a mechanical delay stage (mechanical delay stage) (Newport) and a mechanical chopper is used to omit every second pump pulse. Data acquisition at 1kHz can be achieved by a custom board from Stresing Entwicklunsbüro. For each data point, after 1000 "pump on" and "pump off" shots are accumulated and averaged, differential transmission (ΔT / T) is calculated.
[0077] Due to the group velocity mismatch between the pump and probe wavelengths, there is a reduction in the temporal resolution of the experiment. Based on the rise time of the signal, we estimate the temporal resolution of the experiment to be about 300 fs at 670 nm. Although this is insufficient to study the initial singlet fission process of Pc with sub 100 fs time periods, it is sufficient to study the triplet transfer process.
[0078] Numerical methods: We use a numerical method based on a genetic algorithm to deconvolute the overlapping spectral signals of each excited state and obtain its dynamics. In summary, using the survival of the fittest approach, a large population of random spectra is generated and induced to form a continuous generation of offspring. The best spectrum is returned as the optimized solution. For a given solution, the goodness of fit is calculated as the inverse of the sum of the squared residual and the penalty added for non-physical results. The parent spectra are selected using a tournament method with adaptive crossover. A Gaussian-function mask of random parameters is used to generate offspring.
[0079] According to a third embodiment of the present invention, in an organic light emitting diode, excitons are generated from the charge injected into the active layer. These charges (electrons e- and holes h+) form only 25% of the emission singlet excitons and 75% of the non-emission triplet excitons. Therefore, in the absence of phosphorescence, only 25% of the charge can be converted into light. Under a small portion of the nanocrystals in the active layer, those triplet states can be converted into an emitting substance and produce additional light, such as in Figure 8 Additionally, such an LED will emit at two different wavelengths, opening the possibility for white light emission from a single layer of the composite material.
Claims
1. A photovoltaic device comprising: light capturing device; and neighboring photovoltaic cells; wherein the light-harvesting device comprises an organic semiconductor photoactive layer capable of multi-exciton generation with a luminescent material dispersed therein; wherein the luminescent material comprises an inorganic nanocrystalline semiconductor, the inorganic nanocrystalline semiconductor being passivated by a ligand, the ligand dissolving the inorganic nanocrystalline semiconductor in at least one solvent compatible with the organic semiconductor; wherein the band gap of the inorganic nanocrystal semiconductor is selected to resonate with triplet excitons to non-radiatively transfer the triplet excitons formed by the multi-exciton generation in the organic semiconductor to the inorganic nanocrystal semiconductor via Dexter energy transfer; wherein the adjacent photovoltaic cell is arranged in an emission light path of the luminescent material and has a first photoactive layer; and The band gap of the first photoactive layer matches the band gap of the inorganic nanocrystal semiconductor or is lower than the band gap of the inorganic nanocrystal semiconductor. 2 . The photovoltaic device of claim 1 , wherein the organic semiconductor photoactive layer is capable of singlet exciton fission. The photovoltaic device of claim 2 , wherein the organic semiconductor is an oligoacene. The photovoltaic device of claim 3 , wherein the oligoacene is pentacene or tetracene.
5. A photovoltaic device according to any preceding claim, wherein the organic semiconductor photoactive layer has a bandgap in the range of 2.0 eV to 3.0 eV. 6 . The photovoltaic device of claim 5 , wherein the organic semiconductor photoactive layer has a band gap in the range of 2.2 eV to 2.5 eV.
7. The photovoltaic device of claim 5, wherein the organic semiconductor photoactive layer has a band gap of 2.4 eV.
8. The photovoltaic device of any one of claims 1-4 and 6-7, wherein the band gap of the inorganic nanocrystalline semiconductor is within 0.4 eV of the energy band gap of the triplet excitons.
9. The photovoltaic device of claim 5, wherein the band gap of the inorganic nanocrystalline semiconductor is within 0.4 eV of the energy band gap of the triplet excitons.
10. The photovoltaic device of claim 8, wherein the band gap of the light emitting material is within 0.3 eV of the energy band gap of the triplet excitons.
11. The photovoltaic device of claim 8, wherein the band gap of the light emitting material is within 0.2 eV of the energy band gap of the triplet excitons.
12. The photovoltaic device of any one of claims 1-4, 6-7, and 9-11, wherein the band gap of the light emitting material is in the range of 0.6 eV to 1.6 eV.
13. The photovoltaic device of claim 5, wherein the band gap of the light emitting material is in the range of 0.6 eV to 1.6 eV.
14. The photovoltaic device of claim 8, wherein the band gap of the light emitting material is in the range of 0.6 eV to 1.6 eV.
15. The photovoltaic device of claim 12, wherein the band gap of the light emitting material is in the range of 0.75 eV to 1.3 eV.
16. The photovoltaic device of claim 12, wherein the band gap of the light emitting material is in the range of 0.95 eV to 1.2 eV.
17. The photovoltaic device of claim 1, wherein the inorganic nanocrystalline semiconductor comprises lead chalcogenide nanocrystals.
18. The photovoltaic device of claim 17, wherein the lead chalcogenide nanocrystals are lead selenide or lead sulfide.
19. The photovoltaic device of claim 1, wherein the inorganic nanocrystalline semiconductor comprises any one or more of nanocrystals comprising: CdSe, CdS, ZnTe, ZnSe, PbS, PbSe, PbTe, HgS, HgSe, HgTe, HgCdTe, CdTe, CZTS, ZnS, CuInS2, CuInGaSe, CuInGaS, Si, InAs, InP, InSb, SnS2, CuS, Ge, and Fe2S3.
20. The photovoltaic device of claim 19, wherein the ligand is a small molecule.
21. The photovoltaic device of claim 20, wherein the small molecule is an amine or a thiol.
22. A photovoltaic device according to any one of claims 1-4, 6-7, 9-11 and 13-21, wherein the average distance between the luminescent components of the luminescent material is selected to be similar to the diffusion length of the triplet excitons in the organic semiconductor; wherein the low concentration of the luminescent components minimizes self-absorption by the luminescent components.
23. The photovoltaic device of claim 5, wherein the average distance between luminescent components of the luminescent material is selected to be similar to the diffusion length of the triplet excitons in the organic semiconductor; wherein the low concentration of the luminescent components minimizes self-absorption by the luminescent components.
24. The photovoltaic device of claim 8, wherein the average distance between luminescent components of the luminescent material is selected to be similar to the diffusion length of the triplet excitons in the organic semiconductor; wherein the low concentration of the luminescent components minimizes self-absorption by the luminescent components.
25. The photovoltaic device of claim 12, wherein the average distance between luminescent components of the luminescent material is selected to be similar to the diffusion length of the triplet excitons in the organic semiconductor; wherein the low concentration of the luminescent components minimizes self-absorption by the luminescent components.
26. The photovoltaic device of claim 22, wherein the average distance between the light emitting components is between 10 nm and 2000 nm.
27. The photovoltaic device of any one of claims 23-25, wherein the average distance between the luminescent components is between 10 nm and 2000 nm.
28. The photovoltaic device of claim 26, wherein the average distance between the light emitting components is between 20 nm and 200 nm.
29. The photovoltaic device of any one of claims 1-4, 6-7, 9-11, 13-21, 23-26, and 28, wherein the photovoltaic cell is provided with the first photoactive layer comprising silicon.
30. The photovoltaic device of claim 5, wherein the photovoltaic cell is provided with the first photoactive layer comprising silicon.
31. The photovoltaic device of claim 8, wherein the photovoltaic cell is provided with the first photoactive layer comprising silicon.
32. The photovoltaic device of claim 12, wherein the photovoltaic cell is provided with the first photoactive layer comprising silicon.
33. The photovoltaic device of claim 22, wherein the photovoltaic cell is provided with the first photoactive layer comprising silicon.
34. The photovoltaic device of claim 27, wherein the photovoltaic cell is provided with the first photoactive layer comprising silicon.
35. A photovoltaic device according to any one of claims 1-4, 6-7, 9-11, 13-21, 23-26 and 28, wherein the photovoltaic cell is provided with the first photoactive layer comprising one or more of the following: crystalline silicon, amorphous silicon, copper indium gallium selenide (CIGS), germanium, CdTe, GaAs, InGaAs, InGaP, InP, quantum dots, metal oxides, organic polymers or small molecules or perovskite semiconductors.
36. A photovoltaic device according to claim 5, wherein the photovoltaic cell is provided with the first photoactive layer comprising one or more of the following: crystalline silicon, amorphous silicon, copper indium gallium selenide (CIGS), germanium, CdTe, GaAs, InGaAs, InGaP, InP, quantum dots, metal oxides, organic polymers or small molecules or perovskite semiconductors.
37. A photovoltaic device according to claim 8, wherein the photovoltaic cell is provided with the first photoactive layer comprising one or more of the following: crystalline silicon, amorphous silicon, copper indium gallium selenide (CIGS), germanium, CdTe, GaAs, InGaAs, InGaP, InP, quantum dots, metal oxides, organic polymers or small molecules or perovskite semiconductors.
38. A photovoltaic device according to claim 12, wherein the photovoltaic cell is provided with the first photoactive layer comprising one or more of the following: crystalline silicon, amorphous silicon, copper indium gallium selenide (CIGS), germanium, CdTe, GaAs, InGaAs, InGaP, InP, quantum dots, metal oxides, organic polymers or small molecules or perovskite semiconductors.
39. A photovoltaic device according to claim 22, wherein the photovoltaic cell is configured with the first photoactive layer comprising one or more of the following: crystalline silicon, amorphous silicon, copper indium gallium selenide (CIGS), germanium, CdTe, GaAs, InGaAs, InGaP, InP, quantum dots, metal oxides, organic polymers or small molecules, or perovskite semiconductors.
40. A photovoltaic device according to claim 27, wherein the photovoltaic cell is provided with the first photoactive layer comprising one or more of the following: crystalline silicon, amorphous silicon, copper indium gallium selenide (CIGS), germanium, CdTe, GaAs, InGaAs, InGaP, InP, quantum dots, metal oxides, organic polymers or small molecules or perovskite semiconductors.
41. The photovoltaic device of claim 35, wherein the perovskite semiconductor is an organometallic halide perovskite semiconductor.
42. The photovoltaic device of any one of claims 36-40, wherein the perovskite semiconductor is an organometallic halide perovskite semiconductor.
43. The photovoltaic device of any one of claims 1-4, 6-7, 9-11, 13-21, 23-26 and 28, wherein the photovoltaic cell is provided with the first photoactive layer comprising methylamine lead chloroiodide (CH3NH3PbI2Cl).
44. The photovoltaic device of claim 5, wherein the photovoltaic cell is provided with the first photoactive layer comprising methylamine lead chloroiodide (CH3NH3PbI2Cl).
45. The photovoltaic device of claim 8, wherein the photovoltaic cell is provided with the first photoactive layer comprising methylamine lead chloroiodide (CH3NH3PbI2Cl).
46. The photovoltaic device of claim 12, wherein the photovoltaic cell is provided with the first photoactive layer comprising methylamine lead chloroiodide (CH3NH3PbI2Cl).
47. The photovoltaic device of claim 22, wherein the photovoltaic cell is provided with the first photoactive layer comprising methylamine lead chloroiodide (CH3NH3PbI2Cl).
48. The photovoltaic device of claim 27, wherein the photovoltaic cell is provided with the first photoactive layer comprising methylamine lead chloroiodide (CH3NH3PbI2Cl).
49. The photovoltaic device of any one of claims 1-4, 6-7, 9-11, 13-21, 23-26, 28, 30-34, 36-41, and 44-48, wherein emission from the luminescent material is directed toward the photovoltaic cell.
50. The photovoltaic device of claim 5, wherein emission from the luminescent material is directed toward the photovoltaic cell.
51. The photovoltaic device of claim 8, wherein emission from the luminescent material is directed toward the photovoltaic cell.
52. The photovoltaic device of claim 12, wherein emission from the luminescent material is directed toward the photovoltaic cell.
53. The photovoltaic device of claim 22, wherein emission from the luminescent material is directed toward the photovoltaic cell.
54. The photovoltaic device of claim 27, wherein emission from the luminescent material is directed toward the photovoltaic cell.
55. The photovoltaic device of claim 29, wherein emission from the luminescent material is directed toward the photovoltaic cell.
56. The photovoltaic device of claim 35, wherein emission from the luminescent material is directed toward the photovoltaic cell.
57. The photovoltaic device of claim 42, wherein emission from the luminescent material is directed toward the photovoltaic cell.
58. The photovoltaic device of claim 43, wherein emission from the luminescent material is directed toward the photovoltaic cell.
59. The photovoltaic device of claim 49, wherein emission from the luminescent material is directed to the photovoltaic cell by using a selective wavelength reflecting layer or matching the refractive indices of the layers of the photovoltaic device.
60. The photovoltaic device of any one of claims 50-58, wherein emission from the luminescent material is directed to the photovoltaic cell by using a selective wavelength reflecting layer or matching the refractive indices of the layers of the photovoltaic device.
61. The photovoltaic device of claim 1, wherein at least one step of transferring the triplet excitons to the light emitting material is mediated by non-radioactive Dexter energy transfer.
62. The photovoltaic device of claim 1, wherein the final energy transfer step of transferring the triplet excitons into the light emitting material is mediated by non-radioactive Dexter energy transfer.
63. The photovoltaic device of claim 1, wherein the organic semiconductor is acene, acene dimer, perylene, perylene dimer, perylene diimide, polyester, rayon, thiophene, or a semiconducting polymer.
64. The photovoltaic device of claim 1, wherein the inorganic nanocrystalline semiconductor comprises any one or more of nanocrystals comprising: Organometallic halide perovskite or cesium lead halide perovskite.
65. The photovoltaic device of claim 3, wherein the oligomeric acene is selected from: bis(triisopropyl-silylethynyl) pentacene (TIPS-P), diphenyl pentacene (DPP), diphenyl-4-yl-pentacene (DBP), di(2'-thienyl) pentacene (DTP), and dibenzothienyl pentacene (DBTP), bis(triisopropyl-silylethynyl) pentacene (TIPS-P), bis((triethyl)ethynyl) pentacene (TES-P), rubrene, bis(triisopropyl-silylethynyl) tetracene (TIPS-T), or di(2'-thienyl) tetracene (DTT).
Citation Information
Patent Citations
Materials for solar concentrators and devices, methods and system using them
US20100193011A1
Solar cells based on quantum dot or colloidal nanocrystal films
US20110146766A1